Synthesis method and application of S-type WO3-X-coated CoIn2S4 heterojunction hollow sphere photocatalyst

By preparing S-type WO3-x@CoIn2S4 heterojunction hollow sphere photocatalyst, the problem of low efficiency of existing WO3 photocatalysts was solved, the efficiency of photogenerated carrier separation and the enhancement of reaction sites were achieved, and the catalytic performance of CO2 reduction to CO was significantly improved.

CN120662339APending Publication Date: 2025-09-19HEILONGJIANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510811097.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

The photocatalytic efficiency of existing WO3 photocatalysts is low, the light absorption capacity is insufficient and the photogenerated carriers recombine too quickly, resulting in low light energy utilization efficiency. In addition, the existing synthesis method is complex and not environmentally friendly.

Method used

S-type WO3-x@CoIn2S4 heterojunction hollow sphere photocatalysts were prepared by hydrothermal method and in situ template method. A simple synthetic route was used to construct the heterojunction interface to improve the separation of photogenerated carriers and provide a porous structure to enhance light absorption and reaction sites.

Benefits of technology

The CO2 photoreduction activity of the photocatalyst was significantly improved, the photogenerated carrier separation efficiency and the reactant adsorption performance were enhanced, and the optimized catalyst showed significant catalytic efficiency in the process of CO2 reduction to CO.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662339A_ABST
    Figure CN120662339A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method and application of an S-type WO3-x-coated CoIn2S4 heterojunction hollow sphere photocatalyst, and aims to solve the problem of low photocatalytic efficiency of an existing WO3 photocatalyst. The synthesis method comprises the following steps: 1, dissolving Pb (AC) 2 and Na2WO4 in ethylene glycol, and carrying out solvothermal reaction to obtain a spherical PbWO4 material; 2, dipping the spherical PbWO4 material in a nitric acid solution; 3, carrying out calcination and annealing treatment on the hollow spherical H2WO4; 4, a Co (NO3) 2.6 H2O solution and a 2-methylimidazole solution are injected into the WO3-x suspension, precursor powder is collected, InCl3. 4H2O and TAA are added into a precursor powder mixed solvent, and a solvothermal reaction is carried out; the WO3-x-coated CoIn2S4 heterojunction hollow sphere photocatalyst prepared by the preparation method disclosed by the invention shows excellent CO2 photocatalytic reduction activity under the irradiation of simulated sunlight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a WO 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst preparation method and application. Background Art

[0002] Photocatalytic technology has become an effective solution to energy shortages and environmental pollution problems due to its environmentally friendly, cost-effective and stable performance. It has been widely used in ecological restoration fields such as pollutant decomposition and CO2 conversion. However, existing photocatalytic systems face two key challenges: one is insufficient light absorption capacity, and the other is too rapid recombination of photogenerated carriers. These factors seriously restrict the efficiency of light energy utilization. In order to maintain the continuous progress of the photocatalytic reaction, high-energy lighting devices are usually required, which greatly increases the economic threshold for the application of the technology. Based on this, the development of new photocatalytic materials with excellent performance to break through the existing technical bottlenecks and improve the overall catalytic efficiency has become an important topic in the current research field.

[0003] As a photocatalyst, WO3 exhibits unique performance advantages. Its narrow bandgap of 2.4-2.8 eV enables excellent light absorption in the visible light band, significantly expanding the effective spectral range of photocatalytic reactions. Furthermore, this material combines multiple advantages, including environmental compatibility, chemical inertness, and affordability. Although researchers have developed WO3 nanostructures with various morphologies, significant technical bottlenecks remain in the preparation process: complex synthetic pathways often require specialized templates, diverse precursors, or specific substrates, which not only increases production costs but also contradicts the concept of green chemistry. Furthermore, the self-assembly of nanounits into functional three-dimensional structures through simple methods remains a technical challenge that needs to be addressed. WO3 materials themselves face two key challenges: rapid photogenerated carrier recombination and a relatively low conduction band energy level. These inherent defects significantly affect the material's photocatalytic efficiency. Therefore, developing novel WO3-based composite systems to address these issues has become an important research direction. Summary of the Invention

[0004] The purpose of the present invention is to solve the problem of low photocatalytic efficiency of existing WO3 photocatalysts and to provide an S-type WO 3-x Synthesis method and application of @CoIn2S4 heterojunction hollow sphere photocatalyst.

[0005] The present invention S-type WO 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is achieved by the following steps: 1. Dissolve Pb(AC)2 and Na2WO4 in ethylene glycol and stir thoroughly to obtain a mixed solution. Then transfer the mixed solution to a stainless steel reactor with a polytetrafluoroethylene lining and heat at 150~180 o C, and then cooled to room temperature after the reaction is completed. Spherical PbWO4 material is obtained after washing and drying. Second, the spherical PbWO4 material is immersed in a 3~5mol / L HNO3 solution, and hollow spherical H2WO4 is obtained after washing and drying; 3. In the air atmosphere at 450~550 o The hollow spherical H2WO4 was calcined at a temperature of 300-350 °C and then heated in a H2 / Ar mixed gas environment. o C temperature and annealing treatment to obtain WO 3-x Material; 4. WO 3-x The material was evenly dispersed in methanol solvent to obtain WO 3-x The suspension was prepared with a methanol solution of Co(NO3)2·6H2O and a methanol solution of 2-methylimidazole, and the methanol solution of Co(NO3)2·6H2O and the methanol solution of 2-methylimidazole were injected into the WO 3-x The suspension is allowed to stand for a while, and the reactants are collected, washed, and dried to obtain a precursor powder; The precursor powder was evenly dispersed in a mixed solvent consisting of DMF and ethanol, and then InCl3·4H2O and TAA (thioacetamide) were added at 150~180 o C for 6 to 10 hours, and then washed and dried to obtain S-type WO. 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst.

[0006] The present invention S-type WO 3-x The application of @CoIn2S4 heterojunction hollow sphere photocatalyst is to convert the S-type WO 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst for CO2 photoreduction.

[0007] The present invention S-type WO 3-x The preparation method and application of @CoIn2S4 heterojunction hollow sphere photocatalyst include the following beneficial effects: The present invention prepares WO by simple hydrothermal method and in-situ template method respectively. 3-x Hollow sphere and WO 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst, this method has the advantages of simplicity and high efficiency. 3-xThe @CoIn2S4 heterojunction hollow sphere photocatalyst exhibited excellent CO2 photocatalytic reduction activity under simulated sunlight. Experimental results demonstrated that the S-shaped heterojunction interface significantly improved the separation efficiency of photogenerated charge carriers, while the hierarchical porous structure provided ample active sites and the large specific surface area enhanced the adsorption of reactants. The optimized S-shaped photocatalyst demonstrated remarkable catalytic efficiency in the reduction of CO2 to CO. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 WO prepared in Example 3-x XRD pattern and FT-IR spectrum of @CoIn2S4 composite photocatalyst; Figure 2 TEM image of PbWO4 obtained in Example 1; Figure 3 This is a transmission electron microscope image of H2WO4 obtained in Example 1; Figure 4 WO obtained in Example 1 3-x Transmission electron micrograph of Figure 5 WO obtained in Example 1 3-x Transmission electron microscopy image of @CoIn2S4 composite photocatalyst; Figure 6 WO obtained in Example 3-x (a) UV-visible diffuse reflectance spectrum of @CoIn2S4 composite photocatalyst; (b) corresponding Tauc plot; Figure 7 (a) N2 adsorption-desorption isotherms of different samples obtained in Example; (d) CO2 adsorption isotherms of various samples at 273.15K; Figure 8 The time-yield curves of CO (a) and CH4 (b) under different catalysts were obtained for the examples; Figure 9 The average evolution rate test graph of CO and CH4 of composite catalysts with different ratios was obtained for the example. DETAILED DESCRIPTION

[0009] Specific implementation method 1: S-type WO in this implementation method 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is carried out according to the following steps: 1. Dissolve Pb(AC)2 and Na2WO4 in ethylene glycol and stir thoroughly to obtain a mixed solution. Then transfer the mixed solution to a stainless steel reactor with a polytetrafluoroethylene lining and heat at 150~180 oC, and then cooled to room temperature after the reaction is completed. Spherical PbWO4 material is obtained after washing and drying. Second, the spherical PbWO4 material is immersed in a 3~5mol / L HNO3 solution, and hollow spherical H2WO4 is obtained after washing and drying; 3. In the air atmosphere at 450~550 o The hollow spherical H2WO4 was calcined at a temperature of 300-350 °C and then heated in a H2 / Ar mixed gas environment. o C temperature and annealing treatment to obtain WO 3-x Material; 4. WO 3-x The material was evenly dispersed in methanol solvent to obtain WO 3-x The suspension was prepared with a methanol solution of Co(NO3)2·6H2O and a methanol solution of 2-methylimidazole, and the methanol solution of Co(NO3)2·6H2O and the methanol solution of 2-methylimidazole were injected into the WO 3-x The suspension is allowed to stand for a while, and the reactants are collected, washed, and dried to obtain a precursor powder; The precursor powder was evenly dispersed in a mixed solvent consisting of DMF and ethanol, and then InCl3·4H2O and TAA (thioacetamide) were added at 150~180 o C for 6 to 10 hours, and then washed and dried to obtain S-type WO. 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst.

[0010] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the molar ratio of Pb(AC)2 and Na2WO4 in step 1 is 1:1.

[0011] Specific embodiment three: This embodiment differs from specific embodiment one or two in that the solvent thermal reaction time in step one is 8 to 12 hours.

[0012] Specific embodiment 4: This embodiment differs from any one of specific embodiments 1 to 3 in that the immersion treatment time in step 2 is 45 to 55 hours.

[0013] Specific embodiment 5: This embodiment differs from any one of specific embodiments 1 to 4 in that the calcination treatment time in step 3 is 1.5 to 2.5 hours.

[0014] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the annealing treatment time in step 3 is 1.5 to 2.5 hours.

[0015] Specific embodiment 7: This embodiment is different from the specific embodiments 1 to 6 in that WO 3-x The concentration of the suspension is 1-2 g / L.

[0016] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that WO 3-x The mass ratio of materials, Co(NO3)2·6H2O and 2-methylimidazole is (15~30):(40~60):(120~150).

[0017] Specific embodiment 9: This embodiment differs from any one of specific embodiments 1 to 8 in that the static treatment time in step 4 is 4 to 5 hours.

[0018] Specific embodiment ten: This embodiment differs from specific embodiments one to nine in that the molar ratio of InCl 3 ·4H 2 O to TAA in step four is (1-3):1.

[0019] Example 1: S-type WO in this embodiment 3-x The preparation method of @CoIn2S4 heterojunction hollow sphere photocatalyst is carried out according to the following steps: 1. Dissolve 2mmol of Pb(AC)2 and 2mmol of Na2WO4 in 25mL of ethylene glycol and stir thoroughly. A white precipitate is immediately observed during the mixing process. Then transfer the mixture to a stainless steel reactor lined with polytetrafluoroethylene and heat the reaction system to 160 o C and kept for 10 hours for solvent thermal reaction, and then cooled naturally to room temperature after the reaction was completed. Finally, spherical PbWO4 was obtained after washing and drying; Second, spherical PbWO4 was immersed in 4MHNO3 solution for 48 hours, and then repeatedly washed with deionized water until it reached a neutral state and then dried to obtain hollow spherical H2WO4; 3. Place the hollow spherical H2WO4 at 500 o C in air atmosphere for 2 hours, and then calcined at 300 o Annealing treatment was carried out in a H2 / Ar mixed gas environment for 2 hours to obtain WO 3-x Material; 4. Add 0.02g WO 3-x The material was evenly dispersed in 15 mL of methanol solvent to obtain WO 3-x The suspension was prepared by mixing 10 mL of methanol solution containing 0.046 g of Co(NO3)2·6H2O and 10 mL of methanol solution containing 0.1314 g of 2-methylimidazole. The methanol solution of Co(NO3)2·6H2O and the methanol solution of 2-methylimidazole were injected into the WO 3-xThe mixed solution after sufficient stirring was allowed to stand at room temperature for 4 hours, and after centrifugation and methanol washing, it was placed in an oven for overnight drying to obtain a precursor powder. Subsequently, 0.02 g of the precursor powder was uniformly dispersed in a mixed solvent consisting of 10 mL of DMF and 10 mL of anhydrous ethanol, and 0.0192 g of InCl3·4H2O and 0.0533 g of TAA were added in sequence. After stirring for 20 minutes, the mixture was heated at 160 o C for 8 hours, washed alternately with ethanol and deionized water, and dried to obtain S-type WO 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst (1-WO 3-x @CoIn2S4).

[0020] Example 2: This example is different from Example 1 in that the molar ratio of InCl3·4H2O to TAA in step 4 is 2:1.

[0021] The S-type WO synthesized in this example 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst labeled as 2-WO 3-x @CoIn2S4.

[0022] Example 3: This example is different from Example 1 in that the molar ratio of InCl3·4H2O to TAA in step 4 is 3:1.

[0023] The S-type WO synthesized in this example 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst labeled with 3-WO 3-x @CoIn2S4.

[0024] Figure 1 WO obtained in Example 1 3-x XRD patterns and FT-IR spectra of @CoIn2S4 composite photocatalyst, WO 3-x The XRD diffraction peaks of WO and CoIn2S4 are relatively strong and correspond to the standard card, indicating that WO 3-x It has been successfully compounded with CoIn2S4. 3-x In the FT-IR spectrum of @CoIn2S4 composite material, WO can be clearly observed. 3-x The characteristic absorption peak of WO is confirmed by XRD analysis. 3-x Successful preparation of @CoIn2S4 composite material.

[0025] Figure 2 This is a transmission electron microscope image of PbWO4 obtained in step 1 of Example 1. PbWO4 presents a spherical particle morphology with an average size of about 2 μm, good dispersion characteristics, and a relatively concentrated particle size distribution.

[0026] Figure 3 This is a transmission electron micrograph of the H2WO4 obtained in step 2 of Example 1. The H2WO4 hollow spheres are self-assembled from nanosheet structures and have an overall diameter of approximately 2 μm. This indicates that the effective conversion of the PbWO4 precursor to H2WO4 hollow spheres can be achieved through HNO3 immersion treatment.

[0027] Figure 4 WO obtained in step 3 of Example 1 3-x The transmission electron microscope image shows that the hollow spheres are self-assembled by a large number of nanosheets, which clearly confirms the existence of a hollow structure inside the material.

[0028] Figure 5 WO obtained in Example 3 3-x @Transmission electron microscopy image of CoIn2S4 composite photocatalyst. WO 3-x The @CoIn2S4 material maintains a unique three-dimensional hollow sphere configuration. The number of surface nanosheets on the composite material increases significantly, and the surface roughness is significantly improved.

[0029] Figure 6 WO obtained in Example 3-x (a) UV-visible diffuse reflectance spectrum of @CoIn2S4 composite photocatalyst; (b) corresponding Tauc plot. 3-x @CoIn2S4 heterojunction has significantly enhanced visible light absorption capability.

[0030] Figure 7 (a) N2 adsorption-desorption isotherms of different samples obtained in the examples; (d) CO2 adsorption isotherms of various samples at 273.15K; It shows that WO 3-x @CoIn2S4 has a larger specific surface area and its CO2 adsorption capacity is significantly better than that of a single component.

[0031] Figure 8 The time-yield curves of CO (a) and CH4 (b) under different catalysts were obtained for the examples; by loading CoIn2S4 nanosheets on WO 3-x Surface-constructed WO 3-x @CoIn2S4 composite material, its photocatalytic performance is significantly improved.

[0032] Figure 9 The average evolution rate of CO and CH4 on the composite catalysts with different ratios was obtained for the examples; when the CoIn2S4 loading was too high (3-WO 3-x @CoIn2S4), the catalytic performance decreased, which may be due to the fact that the excess CoIn2S4 hindered the WO 3-xOn the other hand, the CoIn2S4 loading is insufficient (1-WO 3-x @CoIn2S4) cannot provide sufficient active sites, resulting in a weakened CO2 adsorption capacity and ultimately a decrease in CO generation efficiency. Its photocatalytic performance is significantly improved.

[0033] In this embodiment, S-type WO 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst, under simulated sunlight, CO2 molecules are adsorbed and activated on WO 3-x @CoIn2S4 surface. The experimental results show that during the photocatalytic reaction, the main gas products generated are CO and CH4, which confirms the effectiveness of this material in photocatalytic reduction of CO2. 3-x The surface of the catalyst significantly improves the CO2 photoreduction efficiency. 3-x The CO generation rate of CoIn2S4 is much lower than that of the composite binary material. 3-x The @CoIn2S4 composite catalyst exhibited the best CO generation performance, with a yield of 58.71 mol g -1 h -1 The trend of catalytic performance changes is highly consistent with the results of CO2 adsorption experiments, further confirming that the introduction of an appropriate amount of CoIn2S4 can effectively promote the photocatalytic CO2 reduction reaction. The optimized S-type photocatalyst is better than pure WO 3-x The photocatalytic reaction has high CO selectivity by combining CoIn2S4 and CoIn2S4, which can improve the CO yield and selectivity in the CO2 photoreduction reaction. This rational design can not only effectively reduce the recombination of photogenerated charge carriers, but also provide a large specific surface area and abundant reaction sites.

Claims

1. S type WO 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by The S-type WO 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is achieved by the following steps:

1. Dissolve Pb(AC)2 and Na2WO4 in ethylene glycol and stir thoroughly to obtain a mixed solution. Then transfer the mixed solution to a stainless steel reactor with a polytetrafluoroethylene lining and heat at 150~180 o C, and then cooled to room temperature after the reaction is completed. Spherical PbWO4 material is obtained after washing and drying. Second, the spherical PbWO4 material is immersed in a 3~5mol / L HNO3 solution, and hollow spherical H2WO4 is obtained after washing and drying; 3. In the air atmosphere at 450~550 o The hollow spherical H2WO4 was calcined at a temperature of 300-350 °C and then heated in a H2 / Ar mixed gas environment. o C temperature and annealing treatment to obtain WO 3-x Material; 4. WO 3-x The material was evenly dispersed in methanol solvent to obtain WO 3-x The suspension was prepared with a methanol solution of Co(NO3)2·6H2O and a methanol solution of 2-methylimidazole, and the methanol solution of Co(NO3)2·6H2O and the methanol solution of 2-methylimidazole were injected into the WO 3-x The suspension is allowed to stand for a while, and the reactants are collected, washed, and dried to obtain a precursor powder; The precursor powder was evenly dispersed in a mixed solvent consisting of DMF and ethanol, and then InCl3·4H2O and TAA were added at 150~180 o C for 6 to 10 hours, and then washed and dried to obtain S-type WO. 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst.

2. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by In step 1, the molar ratio of Pb(AC)2 and Na2WO4 is 1:

1.

3. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by The solvent thermal reaction time in step 1 is 8 to 12 hours.

4. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by The immersion treatment time in step 2 is 45 to 55 hours.

5. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by In step 3, the calcination treatment time is 1.5 to 2.5 hours, and the annealing treatment time is 1.5 to 2.5 hours.

6. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by Step 4 WO 3-x The concentration of the suspension is 1-2 g / L.

7. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by Step 4 WO 3-x The mass ratio of materials, Co(NO3)2·6H2O and 2-methylimidazole is (15~30):(40~60):(120~150).

8. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by The standing treatment time in step 4 is 4 to 5 hours.

9. The S-type WO according to claim 1 3-x The synthesis method of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by In step 4, the molar ratio of InCl3·4H2O and TAA is (1~3):

1.

10. The S-type WO prepared as claimed in claim 1 3-x The application of @CoIn2S4 heterojunction hollow sphere photocatalyst is characterized by The S-type WO 3-x @CoIn2S4 heterojunction hollow sphere photocatalyst for CO2 photoreduction.

Citation Information

Cited By

  • Three-dimensional WO3 / CdIn2S4 composite heterojunction photocatalytic material as well as preparation method and application thereof

    CN121060563A